Challenges of diversification strategy of RS Capital Holdings Berhad / Faraanida Mobin - Mobin, Faraanida (Faculty of Business and Management, 2008)
In applying the diversification strategy, a particular company first need to ensure that it have what it takes to venture in related or unrelated business. This is because the high risk involved and great challenges ahead. Problems will occur in different angle. With a floating capital of RM 1 million and paid up capital of RM 15 million, the divestment of the businesses by RS Capital Holdings Berhad had seem to lead in the unprofitable areas when they declared that the company suffers losses o the First quarter of the year. Rather than focusing on the major business which is telecommunication industry, the company had taken a risk in venturing into different industries that they are not experience of. This had caused some of manpower cannot be transferable among the parent companies and the subsidiaries. Information through secondary data, personal interviews and observations that have been conducted, the issues or challenges that need to be highlighted in RS Capital Holdings are in terms of its human resources, capital, company’s management, value chain activities and company’s future prospects. As recommendations, the company could probably shut down the operations for the time being of certain subsidiaries and focusing on which is more profitable base on the internal strength.